THE STRUCTURE AND DISTRIBUTION OF CASSAVA FARMER HOUSEHOLD REVENUE IN SITIHARJO VILLAGE, TUGUMULYO SUBDISTRICT, MUSI RAWAS DISTRICT - Arischa, Mona; Arianti, Nyayu Neti; Mulyasari, Gita (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2022)
The purposes of this research are to analyze 1) the structure of cassava farmer household revenue, and 2) the distribution of cassava farmer household revenue in Sitiharjo Village, Tugumulyo Subdistrict, Musi Rawas District. The 50 respondent of this research was taken by Slovin method. This research was conducted on November to December 2017. The results showed that the greatest source of revenue is from off-farm activities, amounting to 46.78%. The unequal level of distribution of cassava farmers' household revenue based on the Gini Ratio (GR) on the source of revenue from on-farm is classified as low inequality with a GR index of 0.29, non-cassava farming (on farm) is classified as high inequality with GR index is 0.80, off-farm is classified as high inequality with a GR index of 0.57, non-farm is classified as high with a GR index of 0.67 and the GR index of all cassava farmer households is 0.39 which is classified as moderate. Based on the criteria of the World Bank (World Bank), cassava farmer households are measured by the share of revenue owned by 40 percent of the population with the low revenue group, which is for the source of revenue from cassava farming receiving 22.92 percent (low category), non-cassava farming. received 0.00 percent (high category), off-farm received 3.10 percent (high category), non-farm received 0.00 percent (high category) and the total of all cassava farmer household revenues received 12.43 percent (medium category).